Implementation of Realistic Mathematics Education Learning Model to Improve Students' Mathematics Learning Outcomes - Odismeri Zega; Yakin Niat Telaumbanua; Yulisman Zega (EDUTEC : Journal of Education And Technology, 2025)
This study aims to enhance student learning outcomes on triangle material by applying the Realistic Mathematics Education (RME) learning model. The research is designed as classroom action research, conducted in two cycles. The findings indicate that the application of RME in mathematics teaching at SMP Negeri 1 Sitolu Ori was effective. In Cycle 1, teacher observations showed an average implementation score of 64.38%, categorized as sufficient, while the student learning outcomes averaged 64.52%, also in the sufficient category, with a 52.38% completion rate. By Cycle 2, teacher observations improved to an average of 85.00%, categorized as good, and student learning outcomes increased to an average of 83.21%, with a 100% completion rate and no unsuccessful students. The results demonstrate that the RME model significantly improved both teaching quality and student achievement, meeting the target of 75% learning completeness.